Komunitas Makrozoobentos di Sungai Batang Ombilin Sumatera Barat - Herdina Putra; - Izmiarti; - Afrizal (Universitas Andalas, 2014)
The study about community of macrozoobenthos at Batang Ombilin River, West Sumatra has been done from November 2012 until March 2013. This study aimed to know the composition and structure of macrozoobenthic community. This research carried out by using survey method and purposive sampling technique. Sampling site determined in six stations. In each station were collected five samples by using Surber net (30x30 cm2). The result showed that community of macrozoobenthos were found 34 species consist of Insecta 20 species, Gastropoda 5 species, Olighocaeta 4 species, Hirudinea 2 species, Lamellibranchiata, Arachnida and Turbellaria one species respectively. The highest relative density was Gastropoda (46.27 %) and the lower was Arachnida (0.28 %). Average population was 130.18 ind/m2, and the highest density has found at Station I (391.07 ind/m2), the lower at Station V (37.77 ind/m2). Dominant species in each station were variated. Average diversity index was 1.73, the highest was found at Station V (H’=2.22) and the lowest at Station III and IV (H’=1.19).The composition of macrozoobenthos among stations were different, with low similarity index ranged from 14.28 % - 36.36 %.Key words : Batang Ombilin, Makrozoobenthos, Composition, Structure.